Análise da utilização da fotografia em produções animadas - Padilha, Humberto Cabral (My University, 2019)
From the popularization of photography and also from animated productions, I propose to analyze selected frames in the movie Spider-Man: Into the Spiderverse. However, it is necessary to review important content for the development and popularization of animation today. In this project I mention important historical points in History of Art, History of Photography, History of Cinema, History of Animation in the world and in Brazil. Following the reviews of contents, and based on the method and analysis proposed by VANOYE (1994): deconstruction, connection, reconstruction of study objects, ara analized 5 frames of the movie by its imagery construction and function inside the plot, as well made comparisons with real photographs of the environment where the story takes place (sic).
A partir da popularização da fotografia e também de produções animadas, proponho a análise quadros selecionados na obra Homem-aranha: No Aranhaverso. Porém antes se faz necessário revisar conteúdos importantes para o desenvolvimento e popularização da animação na atualidade. Nesse projeto cito pontos históricos importantes na História da Arte, História da Fotografia, História do Cinema, História da Animação no mundo e no Brasil. Realizadas as revisões de conteúdos, e a partir do método e análise proposto por VANOYE(1994): desconstrução, conexão, reconstrução de objetos de estudo, são analisados 5 quadros do filme mediante a sua construção imagética e função dentro da trama, assim com são feitas comparações com fotografias reais do ambiente onde a história se passa (sic).
Keywords: Fotografia; Cinema; Arte; Animação (Cinematografia)